Improving Patient Safety: Integrating Data Visualization and Communication Into Icu Workflow to Reduce Cognitive Load. Issue 1 (June 2015) - Faiola, Anthony; Srinivas, Preethi; Hillier, Simon
A decade of emerging bedside information-visualization devices and clinical decision-support systems has provided intensive care unit (ICU) clinicians with a range of tools that display and intelligently filter data in ways that support patient diagnosis. There is an absence, however, of research that adequately addresses the need for visualization tools (related to context-sensitive information) that can reduce cognitive strain during decision-making. In response to this issue, Medical Information Visualization Assistant (MIVA) was designed to contextually organize patient longitudinal data with visual-enhancing tools for easy, rapid and more accurate analysis/interpretation of real-time patient data. MIVA was envisioned as an electronic medical record (EMR) visualization dashboard to reduce cognitive load and related diagnostic error. The current design phase will include communication tools to enhance MIVA's capacity to support ICU team collaboration. In this paper we describe two studies of MIVA that provide insight into its potential as an effective support for clinical work. Quantitative findings show a significant difference in speed and accuracy of MIVA when compared to paper medical charts. Similarly, qualitative outcomes show that participants acknowledge MIVA's potential to reduce cognitive load, while contributing to a rich social matrix of ICU clinical activity that combines work and information flow.